STUDI EVALUASI KINERJA BIDANG USAHA BADAN USAHA MILIK DESA (BUMDes) MUARA UWAI SEJAHTERA DESA MUARA UWAI KECAMATAN BANGKINANG KABUPATEN KAMPAR TAHUN 2017 - Mohd. Arif Rahman; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Based on Law 6 of 2014 concerning Villages, make it clear that villages can establish BUMDes is a Village-Owned Enterprise through direct statements from Village assets that are separated in order to manage assets, services, and other businesses to be managed into community welfare Village. which became the Problem Formulation in the study: first, how to evaluate the performance of the business fields of Muara Uwai Sejahtera BUMDes. second, what influences the performance of the Muara Uwai Sejahtera BUMDes business field.The research was carried out with the First objective, knowing the evaluation of the performance of the business fields of Muara Uwai Sejahtera BUMDes. Secondly, knowing what affected the performance of the business fields of Muara Uwai Sejahtera BUMDes. In its business performance, the Muara Uwai Sejahtera BUMDes do not go according to plan, whereas the only service unit is savings and loans. The theory used in this study is evaluation theory. This research mengunsksn Qualitative methodology with descriptive type of research. The type of data used in this study are primary virgin and secondary data obtained from the results of direct interviews with informants who are willing to know and understand the problems that exist in the field and with documentation.The type of business that is realized is only one in savings and loans for business services. In the Savings and Loans Unit, the delinquency has an impact on the performance of other business sectors, so that 2 (two) other business sectors do not run the trade business and credit businesses.Keywords: Evaluation, Performance, Business Field of BUMDes